Multiple Centres: Thinking About Translation Relations Between the First and Third Worlds - Aveling, Monash and La Trobe Universities, Australia, Harry (Asiatic: IIUM Journal of English Language and Literature, 2010)
In his landmark essay, â€œTranslation and Cultural Hegemony,â€ Richard Jacquemond has asserted that â€œthe global translation flux is predominantly North-North, while South-South translation is almost non-existent and North-South translation is unequal: cultural hegemony confirms, to a great extent, economic hegemonyâ€ (â€œTranslation and Cultural Hegemonyâ€ 139). Jacquemondâ€™s conclusions in his essay have been simplified by Douglas Robinson in his Translation and Empire (31-32) as follows: A dominated culture will invariably translate far more of the hegemonic culture than the latter will of the former. When the hegemonic culture does translate works produced by the dominated culture, those works will be perceived and presented as difficult, mysterious, inscrutable, esoteric and in need of a small cadre of intellectuals to interpret them, while a dominated culture will translate a hegemonic cultureâ€™s works accessibly for the masses. A hegemonic culture will only translate those works by authors in a dominated culture that fit the formerâ€™s preconceived notions of the latter. Authors in a dominated culture who dream of reaching a large audience will tend to write for translation into a hegemonic language, and this will require some degree of compliance with stereotypes. The paper will use the figures provided in the UNESCO Index Translationum for translation in and from South and Southeast Asia to test these various hypotheses.